Clinical characteristics and knowledge of diabetic retinopathy patients at a tertiary hospital in Aceh, Indonesia - Lia M. Zaini; Arief S. Kartasasmita; Tjahjono D. Gondhowiardjo; Maimun Syukri; Putri N. Mulya (African Vision and Eye Health)
Background: Diabetic retinopathy (DR) is a significant microvascular complication of diabetes mellitus, leading to vision impairment and blindness in working-age adults globally.